Smart Dental Revision - Kumar, S. Suraj (Jaypee Brothers Medical Publishers, 2015)
This book "Smart Dental Revision" comprehends the content in eighteen chapters. It covers only those points which are frequently asked in any competitive MDS entrance examination and which are generally missed by the aspirants. This book also discusses the points from which new questions might be asked akin to the previous year's questions. It represents certain difficult points in diagrammatic format for better understanding of the readers. Some of the chapters deliberated in this book are dental material, operative dentistry and prosthodontics, dental histology, dental anatomy, periodontics, orthodontics, oral pathology, etc. The topic endodontics gives a brief description on endodontic microbiology, diseases of pulp, periradicular tissues their diagnosis and treatment plan, bleaching and traumatology. Pedodontics gives a deep knowledge on caries and restorative dentistry, child psychology and miscellaneous. It also deals in-depth with some specialized topics like anatomy, biochemistry, general pathology, microbiology, physiology, pharmacology, general medicine and community dentistry.